Determination of fatty acids in bio-samples based on the pre-column fluorescence derivatization with 1,3,5,7-tetramethyl-8-butyrethylenediamine-difluoroboradiaza-s-indacene by high performance liquid chromatography - Wang, Fei-Hua; Xiong, Xu-Jie; Guo, Xiao-Feng; Wang, Hong; Zhang, Hua-Shan (Journal of Chromatography A, 2013)
•We have designed and synthesized TMBB-EDAN as a new fluorescent labeling reagent for fatty acids (FAs).•TMBB-EDAN has high fluorescence quantum yields (Φ=0.70) and high reactivity with FAs.•An HPLC-fluorescence method was developed for the detection of twelve FAs by using TMBB-EDAN.•The derivatization of TMBB-EDAN with FAs could be completed at room temperature in 30min.•The detection limits for FAs were in the 0.2–0.4nM range. 1,3,5,7-Tetramethyl-8-butyrethylenediamine-difluoroboradiaza-s-indacene (TMBB-EDAN) has been designed and synthesized as a highly fluorescent labeling reagent for carboxylic acids. By using TMBB-EDAN, a sensitive and rapid method based on high performance liquid chromatography-fluorescence detection for the determination of twelve fatty acids (FAs) in bio-samples has been developed. Under optimized conditions, these FAs were tagged with TMBB-EDAN in the presence of 1-ethyl-3-(3-dimethyla-minopropyl) carbodiamide at 20°C for 30min and then the baseline separation was achieved on a C18 column with a linear gradient elution in 26min. With fluorescence detection at λex/λem=490nm/510nm, the linear ranges of FAs were from 3.0 to 300nM and the detection limits with a signal-to-noise ratio of 3 were in the 0.2–0.4nM range. The proposed method offers advantages of milder derivatization condition and much better sensitivity for the determination of FAs, when compared to the reported fluorescence derivatization-based methods.